2014
DOI: 10.1159/000358194
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Posttreatment Drinking Outcomes in Patients with Alcohol Dependence

Abstract: Aim: This cohort study examined how predictors of alcohol dependence treatment outcomes work together over time by comparing pretreatment and posttreatment predictors. Methods: A sample of 274 alcohol-dependent patients was recruited and assessed at baseline, 6 months after treatment initiation (end of the active intervention phase), and 18 months after treatment initiation (end of the 12-month research follow-up phase). At each assessment point, the participants completed a battery of standardized tests [Euro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 48 publications
0
14
1
Order By: Relevance
“…Also in these previous studies, clinical variables did not significantly predict the relapse risk nor showed significant differences between abstainers and relapsers. Moreover, a recent study by Florez et al indicated that the treatment received during the rehabilitation process is more significantly related to the posttreatment outcome than the severity of alcohol dependence at baseline (Flórez et al 2015). Although up to now imaging methods are expensive and complex, they might be a promising tool to strengthen personalized medicine and therefore to be beneficial in terms of cost-value ratio.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in these previous studies, clinical variables did not significantly predict the relapse risk nor showed significant differences between abstainers and relapsers. Moreover, a recent study by Florez et al indicated that the treatment received during the rehabilitation process is more significantly related to the posttreatment outcome than the severity of alcohol dependence at baseline (Flórez et al 2015). Although up to now imaging methods are expensive and complex, they might be a promising tool to strengthen personalized medicine and therefore to be beneficial in terms of cost-value ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Other brain regions that have been shown to strongly respond towards drug-associated cues are the anterior cingulate cortex (ACC), the orbitofrontal cortex (OFC), the ventral striatum (VS), the amygdala and ventral tegmental area (VTA) (Heinz et al 2009). This neurobiological approach appears to be especially promising and recommendable, because clinical markers such as craving, onset of alcohol dependence or lifetime alcohol intake did not provide sufficient information on future relapse (Heinz et al 1996;Flórez et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These methods are used in several applications in different subjects due to their versatility [10][11][12]. References [10,13] show a cost forecast in the early stage of projects, while [11,14] evaluate the suppliers performance. The MRA methods are limited in some cases, like in [9] and in [15].…”
Section: Introductionmentioning
confidence: 99%
“…Of note, a previous study in an outpatient setting also assessed AST, ALT, GGT and MCV with a 1-year follow-up period in a longitudinal naturalistic approach in patients with AD. This study used written informed consent before study participation and reported a subsequent dropout rate of 44% [14]. Table 2 Ranking of baseline variables dependent on the number of significant associations with outcome variables A higher educational level and being employed (as sociodemographic baseline variables) and less use of withdrawal medication, fewer previous hospitalizations and lower breath alcohol levels at admission (as clinical baseline variables) were significantly associated with better treatment outcome (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, higher GGT scores were associated with unfavourable outcomes during and after pharmacotherapy for AD [15,16]. In a longitudinal study assessing post-treatment outcomes in an outpatient sample with one-year follow-up after treatment, higher GGT, AST, ALT, MCV scores and AST/ALT ratios were associated with unfavourable outcomes with regard to drinking-behaviour [14].…”
Section: Introductionmentioning
confidence: 94%